Aplicación de medidas de protección y su importancia en manejo de pacientes con infecciones nosocomiales, área unidad de cuidados intensivos en el Hospital IESS Babahoyo, periodo octubre 2019 – marzo 2020. - Álvarez Jiménez, Jomira Cecibel (2020)
Nosocomial infections occur throughout the world and disturb developed countries and those without resources. Infections acquired in health care centers are among the transcendental origins of death and increased morbidity in hospitalized patients. Objective: To determine the importance of the application of protective measures in the management of patients with nosocomial infections, intensive care unit area at the IESS Babahoyo Hospital, period October 2019 - March 2020. Methodology: This research project uses the descriptive method already This objective is to evaluate certain characteristics of a particular population or situation and thus allow us to work in a systematic and orderly manner in order to determine the importance of protective measures in the management of patients with nosocomial infections. Results: It was possible to show in general that the staff possesses the knowledge that this exposes to many risks by not complying as is due to hospital safety standards, but they were able to state that sometimes by providing immediate service in the event of an emergency or precipitation of Patients do it impulsively and do not take into account the established norms. Conclusions: It was verified in the development of research that there is a surveillance and control plan for the management of patients with nosocomial infections that must be applied more frequently and, therefore, will improve patient care.